Nutritional screening and the impact of malnutrition on poor postoperative outcomes in gynecological oncology patients: NUTRITIONAL SCREENING AND THE IMPACT OF MALNUTRITION IN GYNECOLOGICAL ONCOLOGY - Aynaci, Gülden; Guksu, Zuhal (Progress in Nutrition, 2019)
Background: Sufficient nutrition effects the survival and life quality of gynecologic oncology patients. The prevalence of malnutrition among gynecological cancer patients at the time of their diagnosis is estimated to be 20%. The main aim of the study is to provide the care recommendations that can be applied to any gynecologic surgery clinic to reduce the incidence of malnutrition after surgery and to investigate the effects of malnutrition on the healing process of the patient. We aimed also to improve the nutritional status of inpatients and to increase the awareness of malnutrition in hospitals. Methods: Our study was a prospective study conducted with 403 patients, 334 of whom were oncologic, at the gynecology clinic of the University of Trakya between February 2017- January 2019. Nutritional characteristics were evaluated with NRS-2002 during the preoperative period. Results: The increase in the rate of complications was observed to increase with the risk of malnutrition. It was observed that oncology patients who were hospitalized and operated in gynecology services were at risk for malnutrition. Our study draws attention to the need for nutritional support and follow-up for those at risk of malnutrition. Discussion: To identify patients at risk for malnutrition and to intervene in their nutrition program can help to make significant progress in the patient’s healing process. In our study, we observed that the increase in complication rate led to an increase in the tendency of malnutrition. The rate of gynecologic oncology patients who were at nutritional risk was not to be underestimated. Nutritional support plans of patients with preoperative malnutrition were required to reduce postoperative morbidity and improve long-term patient outcomes. It is therefore important that in gynecological cancer patients the nutritional risk is determined during their hospitalization and so that, trough treatment, malnutrition can be prevented.